LncRNA-mediated regulation of cell signaling in cancer - Peng, W-X; Koirala, P; Mo, Y-Y (Oncogene, 2017)
To date, a large number of long non-coding RNAs (lncRNAs) have been recently discovered through functional genomics studies. Importantly, lncRNAs have been shown, in many cases, to function as master regulators for gene expression and thus, they can play a critical role in various biological functions and disease processes including cancer. Although the lncRNA-mediated gene expression involves various mechanisms, such as regulation of transcription, translation, protein modification, and the formation of RNA–protein or protein–protein complexes, in this review, we discuss the latest developments primarily in important cell signaling pathways regulated by lncRNAs in cancer.